Forward looking loan provisions: Credit supply and risk-taking - Bernardo Morais; Gaizka Ormazabal; José-Luis Peydró; Monica Roa; Miguel Sarmiento (ZBW – Leibniz Information Centre for Economics, 2020)
We show corporate-level real, financial, and (bank) risk-taking effects associated with calculating loan provisions based on expected—rather than incurred—credit losses. For identification, we exploit unique features of a Colombian reform and supervisory, matched loan-level data. The regulatory change induces a dramatic increase in provisions. Banks tighten all new lending conditions, adversely affecting borrowing-firms, with stronger effects for risky-firms. Moreover, to minimize provisioning, more affected (less-capitalized) banks cut credit supply to risky-firms— SMEs with shorter credit history, less tangible assets or more defaulted loans—but engage in “search-for-yield” within regulatory constraints and increase portfolio concentration, thereby decreasing risk diversification.
Keywords: E31; G18; G21; G28; 330; loan provisions; IFRS9; corporate real and credit supply effects of accounting; bank risk-taking